In situ synchrotron X‐ray diffraction investigation of the evolution of a PbO2/PbSO4 surface layer on a copper electrowinning Pb anode in a novel electrochemical flow cell. Corrigendum. (1st May 2015) - Clancy, Marie; Styles, Mark J.; Bettles, Colleen J.; Birbilis, Nick; Chen, Miao; Zhang, Yansheng; Gu, Qinfen; Kimpton, Justin A.; Webster, Nathan A. S.
Abstract : Figures 7 and 8 of the article byClancy et al. [(2015), J. Synchrotron Rad.22, 366375 ] are corrected.